HIV voluntary counselling and testing for African communities in London: learning from experiences in Kenya. Issue 7 (2nd October 2007) - Prost, A; Sseruma, W S; Fakoya, I; Arthur, G; Taegtmeyer, M; Njeri, A; Fakoya, A; Imrie, J
Abstract : Objectives: To explore the feasibility and acceptability of translating a successful voluntary counselling and testing (VCT) service model from Kenya to African communities in London. Methods: Qualitative study with focus group discussions and a structured workshop with key informants. Five focus group discussions were conducted in London with 42 participants from 14 African countries between August 2006 and January 2007. A workshop was held with 28 key informants. Transcripts from the group discussions and workshop were analysed for recurrent themes. Results: Participants indicated that a community-based HIV VCT service would be acceptable to African communities in London, but also identified barriers to uptake: HIV-related stigma, concerns about confidentiality, and doubts about the ability of community-based services to maintain professional standards of care. Workshop participants highlighted three key requirements to ensure feasibility: ( a ) efficient referrals to sexual health services for the newly diagnosed; ( b ) a locally appropriate testing algorithm and quality assurance scheme; ( c ) a training programme for VCT counsellors. Conclusions: Offering community-based VCT with rapid HIV tests appears feasible within a UK context and acceptable to African communities in London, provided that clients' confidentiality is ensured and appropriate support is given to the newly diagnosed. However, the persistence of concerns related to HIV-related stigma among African communities suggests that routine opt-out testing in healthcare settings may also constitute an effective approach to reducing the proportion of late diagnoses in this group. HIV service models and programmes from Africa constitute a valuable knowledge base for innovative interventions in other settings, including developed countries.